Comolia paraensis (Melastomataceae), a striking new species of Marcetieae endemic to Pará, Brazil - Da Silva, Diego Nunes; Da Rocha, Maria José Reis; Guimarães, Elsie Franklin; Guimarães, Paulo José Fernandes (Phytotaxa, 2024)
During the preparation of the taxonomic review of Comolia, some taxonomic novelties were found. Here we describe Comolia paraensis, a new species endemic to the Brazilian state of Pará, preliminary categorized as Endangered. This species occurs in the campinas around Oriximiná and in the stony Amazonian savannas of Monte Alegre and Óbidos. Comolia paraensis is morphologically similar to C. kuhlmannii and C. veronicifolia, two taxonomic entities that here were considered distinct from C. villosa. Comolia paraensis is illustrated, compared with similar species, and notes on its geographic distribution and preliminary conservation status are provided. We also discuss the succulence found in the branches of the population from Monte Alegre, something unprecedented within Marcetieae, but commonly reported in Pyramieae and Sonerileae.